Characterizing the fecal microbiome in patients on the ketogenic diet for drug resistant epilepsy - Alexander Freibauer; Nikhil Pai; Rajesh RamachandranNair (Heliyon)
Background: The ketogenic diet is a dietary therapy with anti-seizure effects. The efficacy of the diet is variable, with initial animal studies suggesting the intestinal microbiome may have a modulating effect. Initial research on the role of the human microbiome in pediatric epilepsy management has been inconclusive. Methods: In this single-center prospective cohort study, stool samples were collected from 4 patients with drug resistant epilepsy on the ketogenic diet and 9 with drug resistant epilepsy as controls. The samples were analyzed by 16S RNA sequencing. Results: A trend towards increased alpha diversity was noted among patients on the ketogenic diet compared to the control group. Patients on the ketogenic diet also trended towards a higher relative abundance of Bacteroidaceae, Ruminococcaceae, and Prevotellaceae species. A subset of the control group had a high relative abundance of Bifidobacterium, which may make them a candidate for a trial of the ketogenic diet as a therapeutic option. Conclusion: These findings add to the growing field of research of how the ketogenic diet modulates the intestinal microbiome in pediatric epilepsy patients. Future emphasis on multi-centre trials, consistent stool collection practices and the establishment of standardized stool biobanking protocols are needed further to validate these novel findings in a pediatric population.